Chester Barnard's systems-theoretic approach to organisation theory: a reconstruction. Issue 5 (3rd September 2021) - Valentinov, Vladislav; Roth, Steffen
Abstract: Chester Barnard's organisation theory is widely acknowledged to be grounded on a systems-theoretic approach which has however remained largely inchoate. The present paper ventures a hypothetical reconstruction of this approach by identifying the salient parallels between Barnard's thought and Niklas Luhmann's theory of social systems as well as Alfred North Whitehead's philosophy of organism. While these parallels are by no means perfect, Barnard seems to have anticipated the Luhmannian view of organisations as complexity-reducing systems navigating a precarious outer environment. Drawing on Whitehead, Barnard argued that organisations may succeed with this task insofar as they operate as organismic wholes.